Book review: Birgit Weyel, Wilhelm Gräb, Emmanuel Lartey and Cas Wepener (eds.). International Handbook of Practical Theology (Nordic Journal of Practical Theology, 2023)
Book review: Birgit Weyel, Wilhelm Gräb, Emmanuel Lartey and Cas Wepener (eds.). International Handbook of Practical Theology.